Effectiveness of Povidone Iodine and Antibiotic Treatment on Postpartum Reproductive Disorders in Beef Cattle - Setyawan Erif Maha Nugraha; Adi Yosua Kristian; Gustari Sri; Kusumawati Asmarani; Budiyanto Agung; Prihatno Surya Agus (BIO Web of Conferences, 2021)
This research was conducted to find out the reproductive disorders of postpartum and the effectiveness of its treatment in various nations of beef cattle. A total of 30 beef cattle raised in cattle groups in the D.I.Y. area was used as research samples. Cows are divided into three groups namely control group, iodine povidone infusion group, and antibiotic infusion group. First, second, and third months postpartum are performed clinical examination, blood collection, and rectovaginal examination. Haematological and clinical conditions in postpartum beef cattle have variations but most show a high profile of leukocytes in 1 st to 5th week. Povidone iodine infusion treatment in 1 st week postpartum can reduce bacterial infection until 5th week and can accelerate the uterine involution process during the recovery period.